El material didáctico "MY MAGIC TREE" y su influencia en el aprendizaje cognitivo en los niveles: memoria, análisis y comprensión de los .estudiantes del 6º grado del nivel primario de la I.E. Nº 0106-Atumpampa, Tarapoto, 2012 - Macedo Piña, Cinthia (2013)
This research was made to determinate the influence of the didactic material "My Magic Tree" on the levels of the cognitive learning: memory, analysis and understanding of the sixth grade of primary level in the Educational lnstitution Nº 0106- ATUMPAMPA, Tarapoto. This research was developed in the Educational lnstitution Nº 0106- ATUMPAMPA in Tarapoto city, San Martin Department, Peru. For this research project, pre and post tests were applied at the beginning and the end of each class. The pre and post tests were designed with fifty questions divided into three levels to measure student's cognitive learning in the sixth grade of primary level. We also had, as a principal means of teaching, a meter ... and-a-half tree made from cardboard, carefully designed in order to improve the teaching and learning process of a second language. According to the results of this research, they show that the didactic material "My Magic Tree" has significantly influenced on the students as it could be seen in the graphic Nº 01 which shows a great improvement •between pre-test an post-test. The results of this research show us that there is a great significant students' progress, for that reason the results of the hypothesis test rejects the null hypothesis and accept the research hypothesis. From the paragraphs above, it has been demonstrated that the didactic material "My Magic Tree" has taken significant in the cognitive learning, in the levels: memory, analysis and understanding in the students of sixth grade primary of the Educational lnstitution Nº 0106-ATUMPAMPA, Tarapoto. This is proved in the graphic Nº 01.